ANALISING THE RELATIONSHIP BETWEEN GENDER DISCRIMINATION AND EMPLOYEE PERFORMANCE AT PT. HASJRAT ABADI SUDIRMAN MANADO - Pakasi, Chelsea Wanda (Sam Ratulangi University, 2016)
Employee is an important thing in company or organization. It plays vital role because performance of the company or organization depends on their employee performance.Â One of the factors that can affect is discrimination. Discrimination can also occur in the workplace such as gender discrimination. The purpose of this research is to analyze the relationship between gender discrimination and employee performance in PT. Hasjrat Abadi. The targets of population were the employees at PT. Hasjrat Abadi Sudirman, Manado. And the sample takes 10 employees representing of each department. Method that is used in this research is qualitative method. Data was collected using interview. The result from the study found thatâ€™s discrimination gender and the performance of employee donâ€™t have a significant increase. The study recommended the company should deeply observe the quality of employee without stereotyping and building more trust between company and employees.